Case Report: Two clinical cases of severe deep infiltrating endometriosis with infertility—transplantation first or surgery first? Natural cycle or artificial cycle? - Tang, Fei; He, Ye; Guo, Peipei; Wang, Yue; Liu, Yunyun; Wang, Liting; Wang, Yi; Xie, Pengxiang; Fang, Youyan; Li, Caihua; Yu, Zhaojuan; Li, Xuqing; et al. (Frontiers in Medicine, 2025)
Deep infiltrating endometriosis (DIE) is a severe condition frequently linked to infertility, yet the optimal integration of surgery and assisted reproductive technology (ART) remains controversial. This study reports two cases of infertility secondary to severe rectal DIE that achieved live births through a tailored, sequential strategy. The management paradigm consisted of three phases: (1) fertility preservation via embryo cryopreservation, (2) definitive laparoscopic surgical resection, and (3) a natural-cycle frozen embryo transfer (NC-FET). Postoperatively, both patients demonstrated a significant decline in CA125 levels and substantial clinical improvement. The first case involved a 27-year-old with primary infertility, while the second, more complex case involved a 31-year-old with ureteral DIE and hydronephrosis, requiring multidisciplinary surgery. These cases illustrate that an integrated approach, which strategically combines preoperative fertility preservation, radical surgery to rectify pelvic anatomy, and a physiological, hormone-free embryo transfer, can optimize the likelihood of achieving pregnancy in patients with symptomatic infertility due to severe DIE.